LF-NMR intelligent evaluation for lipid oxidation indices of polar compound distribution, fatty acid unsaturation, and dynamic viscosity: Preference and mechanism. (November 2022) - Li, Xu; Xing, Changming; Wang, Zhisheng; Sun, Wenxing; Wu, Chengfei; Xu, Guangfei; Wang, Xingguo
Graphical abstract: Highlights: Ability of LF-NMR for the aging evaluation of edible oil was proved. LF-NMR preferred to reflect information of fatty acid than triglyceride. Two mechanisms for the LF-NMR method were summarized. Signal peak 21 represented polar and low-molecular-weight products. Abstract: The Low Field Nuclear Magnetic Resonance (LF-NMR) intelligent analysis for lipid oxidation indices of polar compound distribution, fatty acid unsaturation, and dynamic viscosity was established and compared. LF-NMR curves obtained from the multivariate approach were more suitable for the establishment of prediction models. Results proved the ability of LF-NMR for the aging evaluation of edible oil, but different prediction performance was found for various indices. The order from the good to bad prediction was: fatty acid unsaturation > polar compound > dynamic viscosity. It demonstrated the preference of LF-NMR for reporting the information of fatty acid than triglyceride in oxidized oil. Two mechanisms for the LF-NMR method were summarized and expressed by equations. Results also supported that the peak 21 in the LF-NMR curve provided unique information about polar and low-molecular-weight products rather than polymer compounds. Data were expected for a better understanding of LF-NMR signals and to accelerate its wide application in the food industry.